Moving targets - Easley, Warren C. (Easley, Warren C. Cal Claxton Oregon mysteries., 2018)
Claxton has no idea that his new client will turn his life upside down. As he begins to investigate, he starts finding links between his cases and the possibility of a lucrative riverfront project and a foreign assassin. And in a separate battle, he recruits neighbors to stop the reboot of a quarry operation that threatens his farmhouse home in rural Dundee.